Business Process Re-engineering and its Role of Achieving Competitive Advantage: An application study in the State Company of Vegetable Oil Industry (Journal of Accounting and Financial Studies ( JAFS ), 2014)
The business process re-engineering is one of the popular concepts at this time because its provide a radical solution for the problems that companies faces. This method appeared because the changes of competition and costumers 'desires at the two last decades. The markets become wider because of the globalization so the companies must change its way to stay a life.        The research aim is to concentrate on the  BPR  because it's a  philosophy aims to re-organize the company's business process to achieve the competitive advantage, the research also aims to a plicate  the BPR using cost management technique  in the State Company of Vegetable Oils Industry.     The research importance is applying the BPR using strategic cost management to achieve the competitive advantage for the selected company.       The main research hypothesis is applying BPR using the strategic cost management will reduce the cost, improve quality and reduce time and achieving competition advantage.       The most important conclusion that BPR is a radical concept for change to the companies that couldn't compete in the current environment, so these companies should change their strategies to achieve requirement like process flexibility and customer needs.       The important recommendation is if these state companies can work according to the market demand and competition, doing the necessary improvement so they can compete other company's products with making radical changes relevant with new environment.